2017
DOI: 10.1177/1479164117710446
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide: A predictor of cardiovascular mortality in subjects with established atherosclerotic disease

Abstract: C-peptide was associated with cardiovascular mortality independently of known diabetes status in a cohort of patients with chronic atherosclerotic disease. Future studies using C-peptide into a reclassification approach might be undertaken to consider its potential as a cardiovascular disease biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 8 publications
1
23
0
1
Order By: Relevance
“…Previously published results have shown C-peptide to be associated with insulin resistance, cardiometabolic abnormalities belonging to the metabolic syndrome, dyslipidemia, hypertension, hyperuricemia, and type 2 diabetes mellitus in both obese children and adults [42, 43]. Cardellini et al [44] demonstrated an important role of C-peptide levels in the chemotactic effect on the inflammatory cells and suggested that it promotes the onset of atherosclerosis. To the best of our knowledge, this is the first study addressing C-peptide as potential indicator of MUO in overweight/obese children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published results have shown C-peptide to be associated with insulin resistance, cardiometabolic abnormalities belonging to the metabolic syndrome, dyslipidemia, hypertension, hyperuricemia, and type 2 diabetes mellitus in both obese children and adults [42, 43]. Cardellini et al [44] demonstrated an important role of C-peptide levels in the chemotactic effect on the inflammatory cells and suggested that it promotes the onset of atherosclerosis. To the best of our knowledge, this is the first study addressing C-peptide as potential indicator of MUO in overweight/obese children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The Tor Vergata Atherosclerosis Registry (TVAR) (ISRCTN42405215) was previously described [21]. Here, we show a secondary analysis based on follow-up performed in 2017.…”
Section: Description Of Patientsmentioning
confidence: 99%
“…DST200-R&D Systems, Inc.); the average intra-assay coefficient of variation was 5.6% and interassay coefficient of variation was 17.3%. Other laboratory measurements were previously described [21]. GFR was estimated with the MDRD formula.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Here t is a time-horizon of interest, which is specified by the user, and so is threshold c. Examples in different areas of clinical research are reported in Pignatelli et al (2015), Iacovelli et al (2015), Riggio et al (2015), Basili et al (2017) and Cardellini et al (2017). Suppose now that we are actually measuring a time-dependent marker X (t), which has been repeatedly assessed for n subjects at pre-specified visit times…”
Section: Prognostic Accuracy Of Functions Of Trajectories Of Longitudmentioning
confidence: 99%